Exploring the Impact of Photovoice on Self-Expression in English Language Learning: A Systematic Literature Review - Adawiyah, Dita; Larasaty, Finza; Sulistiyo, Urip; Abrar, Mukhlash (PPSDP International Journal of Education, 2024)
This systematic literature review explores the impact of Photovoice on fostering self-expression among English language learners and identifies the key challenges in implementing this participatory visual methodology within classroom settings. Using the PRISMA method, this review analyzes peer-reviewed studies published between 2019 and 2024. A total of 270 articles were initially identified through databases such as Scopus and Google Scholar, with 9 studies selected for thematic analysis focused on self-expression and the integration challenges of Photovoice in English language learning. The findings demonstrate that Photovoice significantly enhances self-expression in students by enabling them to confidently articulate complex emotions and ideas in English, reducing language anxiety, and promoting deeper engagement. However, obstacles such as limited classroom time, inadequate technological resources, and insufficient teacher training were noted as barriers to its effective implementation. This review addresses a critical gap in the literature by focusing specifically on the role of Photovoice in fostering self-expression in English learners, an area that remains underexplored. The study contributes to educational practice by providing educators with insights into how Photovoice can be integrated into language teaching to enhance self-expression, while also highlighting the practical challenges and offering recommendations for overcoming them to maximize the method’s potential.